(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Every year, over 800,000 people worldwide die by suicide, with men having a suicide rate twice that of women in India, though women are more likely to attempt suicide. Menstruating women experience pain and mood swings, and 5% suffer from premenstrual dysphoric disorder (PMDD), a severe form of premenstrual syndrome (PMS) that includes depression. The study explores the relationship between menstrual cycle phases and suicide, using a cross-sectional comparative design. It compared 50 women who committed suicide with 50 who died of other causes, analysing menstrual cycle phases through histopathological examination of cadaveric uteruses. Results showed that hanging was the most common suicide method, with the highest rate in women aged 15- 30. Psychiatric illness was the primary motive, found in 34% of cases. The study found no significant correlation between menstrual cycle phases and completed suicides, nor was PMDD a major factor. The distribution of menstrual phases was similar between study and control groups, and marital status did not significantly relate to suicides. More suicides occurred among women below the poverty line compared to the control group.